Reinforced concrete : mechanics and design - MacGregor, James G.; Wight, James K. (Singapore : Pearson Education South Asia Pte Ltd, 2005)
Explains the theory and practice of reinforced concrete design with many examples, illustrations, and photographs. This book focuses on preparing students to make judgment decisions required in reinforced concrete design, and reflects the author's experience as a teacher of reinforced concrete design and as a member of various code committees.
1. Introduction. 2. The Design Process. 3. Materials. 4. Flexure: Basic Concepts, Rectangular Beams. 5. Flexure: T Beams, Beams with Compression Reinforcement, and Special Cases. 6. Shear in Beams. 7. Torsion. 8. Development, Anchorage, and Splicing of Reinforcement. 9. Serviceability. 10. Continuous Beams and One-Way Slabs. 11. Columns: Combined Axial Load and Bending. 12. Slender Columns. 13. Two-Way Slabs: Behavior, Analysis, and Direct Design Method. 14. Two-Way Slabs: Equivalent Frame Method. 15. Two-Way Slabs: Elastic, Yield Line, and Strip Method Analyses. 16. Footings. 17. Shear Friction, Horizontal Shear Transfer, and Composite Concrete Beams. 18. Discontinuity Regions, Strut-and-Tie Models. 19. Walls, Shear Walls and Lateral Forces on Buildings. 20. Design for Earthquake Resistance. Appendix A: Design Aids. Appendix B: Notation. References. Index.
Includes bibliographical references and index.
Keywords: Flexure : Basic Concepts, Rectangular Beams; The Design Process